Christian mission, contextual theology, prophetic dialogue : essays in honor of Stephen B. Bevans, SVD - Irvin, Dale T., 1955-; Phan, Peter C., 1943-; Bevans, Stephen B., 1944- (The American Society of Missiology ;, 2018)
"While the intent of the editors is to honor Steve Bevans, SVD, a towering figure in the field of missiology and a longtime author of Orbis books on missiology, this book will be designed less as a festschrift than as a textbook for classroom use. Designed around the three main foci of Bevans' theology (mission, contextual theologies, and dialogical theory), it will appeal to teachers of courses in Christian mission, theological method, contextual theologies, and contemporary Third World theologies. The contributors are a who's who of contemporary mission studies in a global context, including representatives from various Christian traditions and from throughout the global church"--